Study on the optimization of the process of extracting Polyporus umbellatus polysaccharides by ultrasonic-assisted ionic liquid and its antioxidant activity - ZHU Miao; LI Zhizhou; LIU Junhai; LEI Xiaoyun (Shipin yu jixie)
ObjectiveThis study aimed to develop an efficient extraction process for polysaccharides from southern Shaanxi Polyporus umbellatus using ultrasonic-assisted ionic liquid extraction and evaluate the antioxidant activity of the extract.MethodsUse the ultrasonic auxiliary ionic liquid method to extract poronalt polysaccharides, and conduct five-level orthogonal experiments on the basis of single-factor testing. Examine the effects of extracting time, extraction temperature, material liquid ratio and 1-ethyl-3-methylimramidazole acetate quality concentration of the extraction rate of pomollagium polysaccharides.Optimize the process of extracting the poriaon polysaccharide in the liquid liquid of the ultrasonic auxiliary ion liquid. Additionally, the DPPH free radicals clearance and OH free radicals to remove the antioxidant capacity of poronaldium polysaccharides.ResultsOptimal extraction conditions were achieved with a 60 min ultrasonic time, extraction temperature of 70 ℃, a solid-to-liquid ratio of 1:25 (g/mL), and a [EMIM]AC was 3 g/L. Under this condition, the extraction rate of polymal polysaccharides is 8.74%. The extracted polysaccharides showed significant antioxidant activity, effectively scavenging DPPH and OH free radicals.ConclusionThe Ultrasonic-Assisted Ionic Liquid extraction process is efficient and feasible for extracting P. umbellatus polysaccharides, yielding a high extraction rate and strong antioxidant activity. This method enhances the potential application of P. umbellatus polysaccharides as natural antioxidants.